Achieving party unity in the Netherlands: Representatives' sequential decision-making mechanisms at three levels of Dutch government. (September 2019) - van Vonno, Cynthia MC
How do parties at different levels of government get their representatives to vote according to the party line? Employing the sequential decision-making approach to party unity, we explore the relative importance of cue-taking, party agreement, party loyalty, and party discipline as individual representative decision-making mechanisms. On the basis of the Dutch version of the PartiRep comparative Member of Parliament survey, we find few differences between national and subnational representatives when it comes to the first two mechanisms, but party loyalty and party discipline seem to play a less important role in determining representatives' decision whether to vote with the party group line. This is, in part, in line with our theoretical expectation that subnational representatives are less likely to be motivated by office-seeking and vote-seeking than their national counterparts.